Phraseological field with the hyporonym friendship: semantic differentiation (on the basis of modern English communicative phraseological units); Коммуникативные аспекты языка и культуры; Ч. 1 - Grekhova M. (Актуальные проблемы лексикологии, фразеологии, 2015)
Заглавие с титульного экрана